Theory of structure and thermodynamic function of liquid 4He (Review Article): Сверхтекучий 4He и 3He - Vakarchuk, I.O.; Pastukhov, V.S.; Prytula, R.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
A new method of calculation of the density matrix of a many-boson system is proposed. The calculation of thermodynamic and structure functions at finite temperatures based on density matrix of Bose liquid is made. The structure factor of liquid 4He at T = 0 K is used as an input information for numerical calculation instead of the interatomic potential. We found a good agreement of the calculated quantities with experimental data.